Effect of year and irrigation on yield and quantity of different potato varieties - Ábrahám, Babett Éva; Sárvári, Mihály (Acta Agraria Debreceniensis, 2006)
dramatically in the last few decades. We are lagging behind Western European countries as regards yields. The ecological conditions are not favourable for potato, but the low yields other causes: the use of non-suitable seed, the low level of irrigation and nutrient supply and out of date machinery. The competitiveness of production is further decreased by the great alternation in yields from year to year, unpredictable market conditions, poor consumption habit, and often the lack of quality products. The experiment was carried out at the experimental site of the University of Debrecen, Farm and Regional Research Institute, at Látókép. In our experiment, we examined the yield and selected quality parameters of 9 medium-early varieties in large parcels. Of the examined varieties, 3 are of Dutch, and 6 are of Hungarian breeding. The experiment was set up in 2004 and 2005, on 50 m2 parcels on calcareous chernozem soil after winter wheat (2004) and two rowed barley (2005) as a forecrop. The varieties were examined in 4 repetitions in randomized blocks, of which two repetitions were irrigated, and two were non-irrigated. We examined the yields of the varieties, the distribution of tubers according to size and their percentages and changes, and selected parameters of quality and chemical composition due to irrigation. We studied the dry matter content, the starch content, the underwater mass, the amount of reducing sugars, and the colour index of frying of the tubers. Summary, it can be stated that among the agrotechniques, year effect, variety and irrigation factors have considerable impact on potato yield quality and quantity. However, the impact of irrigation depends on the year effect.